(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article presents a linguocognitive and cultural analysis of antonymous (opposite) proverbs in Uzbek and English. The primary aim of the study is to explore folk cognition, social values, and worldview through opposite expressions. The results indicate that, although universal cognitive tendencies exist in both languages, cultural context and language-specific features play a decisive role in the formation of proverbs. Comparative analysis provides new perspectives for linguocultural studies and linguistic research.